The impact of multidrug therapy on the epidemiological pattern of leprosy in Juiz de Fora, Brazil O impacto da poliquimioterapia no perfil epidemiológico da hanseníase em Juiz de Fora, Brasil - Luzivander S. Soares; Rodrigo de O. Moreira; Vanessa V. Vilela; Márcio J. M. Alves; Ana Flávia M. Pimentel; Ana Paula Ferreira; Henrique C. Teixeira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
We investigated the impact of multidrug therapy (MDT) on the epidemiological pattern of leprosy in Juiz de Fora, Brazil, from 1978 to 1995. Evaluation of 1,283 medical charts was performed according to the treatment regimen used in two different periods. Following the introduction of MDT in 1987, prevalence of leprosy decreased from 22 patients/10,000 inhabitants to 5.2 patients/10,000 inhabitants in 1995. Incidence rate of leprosy was lower in period II (1987-1995) than in period I (1978-1986). Decreasing prevalence and incidence appear to be related to drug efficacy rather than decreased case identification, since both self-referred and professionally referred treatment increased markedly from period I to period II. For both periods, multibacillary leprosy was the most frequent clinical form of the disease (±68%), and the main infection risk factor identified was household contact. Leprosy is predominantly manifested in adults, but an increase in the number of very old and very young patients was observed in period II. The MDT program has been effective both in combating leprosy and in promoting awareness of the disease. Investigamos o impacto da poliquimioterapia (PQT) no perfil epidemiológico da hanseníase em Juiz de Fora, Brasil, de 1978 a 1995. Fizemos uma avaliação de 1.283 prontuários, de acordo com o esquema terapêutico adotado em dois diferentes períodos. Desde a introdução da PQT, em 1987, a prevalência da hanseníase caiu de 22 pacientes/dez mil habitantes para 5,2 pacientes/dez mil habitantes em 1995. A incidência da doença foi menor no período II (1987-1995) em comparação ao período I (1978-1986). A diminuição da prevalência e da incidência está mais relacionada à eficácia das drogas que a uma queda na identificação da infecção, já que tanto a procura espontânea quanto os encaminhamentos aumentaram significativamente do período I para o período II. Em ambos os períodos, a forma clínica mais freqüente foi a multibacilar (±68%), e o contato intradomicilicar foi o maior fator de risco conhecido associado à infecção. Um aumento de pacientes muito velhos ou muito novos foi observado no período II. Os resultados indicam que o esquema PQT tem sido eficaz no combate à hanseníase e tem aumentado a conscientização e o conhecimento da doença.